Assessing the cost‐effectiveness of interventions within a humanitarian organisation. Issue 3 (22nd April 2019) - Puett, Chloe
Abstract : Cost‐effectiveness analysis is increasingly relevant in humanitarian action. The cost of response has increased exponentially in the past decade, alongside concurrent donor budget restrictions. However, there remains limited comprehension and application of these methods in this field. This paper documents methods developed for use within Action Against Hunger, an international humanitarian organisation, in response to a lack of understanding of this topic within the humanitarian community and limited evidence of the cost‐effectiveness of humanitarian action. These methods encompass costs to both implementing institutions and participating communities. Activity‐based cost analyses are conducted to assess resources per programme activity. Cost‐effectiveness is evaluated using successful programme outcomes, and uncertainty is appraised via sensitivity analysis. This paper aims to advance knowledge, stimulate discussion, and promote the adoption of cost‐effectiveness methods for building the evidence base for humanitarian action, including consideration of community costs, to enable analytical outputs that are useful for managers and policymakers alike.